Efficacy, Use, and Usability of the VIP-HANA App for Symptom Self-Management in PLWH with HANA Conditions - Schnall, Rebecca (AIDS Behav, 2021)
The purpose of this study was to evaluate the efficacy of the VIP-HANA application (app) for improving symptom burden in a randomized control trial of 100 people living with HIV (PLWH) who have non-AIDS conditions associated with HIV. The intervention group received the VIP-HANA app which allowed them to report their symptoms every week and receive self-management strategies tailored to their symptoms. The control arm received an app to report their symptoms every week but did not receive any strategies. The results of our study suggest that symptom burden improved in the participants of both study arms. Although these findings do not support the efficacy of VIP-HANA in improving symptom burden in PLWH who have HANA conditions, this could be a function of the study design. Findings suggest that PLWH are interested in monitoring their symptoms, which could have implications for the wider use of digital health for patient surveillance.